Correlation Analysis of Self-Concept and Interpersonal Communication Among Generation Z Nursing Students at Pre-Professional Nursing Practice - Paramitha, Dewi Setya; Amaliah, Noor; Ariadi, Herman (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: Interaction between people is facilitated by communication. The self concept might take on a positive or negative form. Gen Z is unique among current generations. Not just for the social structure they have come up in, but also for their spending habits, which differ from other generations. Objective: to investigate the possible relationship between generation Z nursing students' interpersonal communication skills and their self concept. Methods: A cross-sectional approach to correlation analysis was used in the research technique. The instruments were questionnaires and observations. The research sample consisted of 70 seventh semester preprofessional nursing students from Banjarmasin, selected using a total sampling technique. The Spearmen Rank Correlation test was utilized in this investigation. Results: indicated that 95.7% of students exhibited a good self concept, whereas 78.6% of students had intermediate levels of interpersonal communication abilities. The statistical test results showed a significant link (p < 0.05) between nursing students' self concept and their interpersonal communication skills. Conclusion: Students have a positive self concept, but clinical practice experience and social media influence their interpersonal communication skills. Suggestion: It is necessary to develop a program to improve both the positive nursing student’s self concept and teaching learning methods suitable for Z generation nurses to their communication abilities.